2019
DOI: 10.1108/jarhe-07-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception and use of English in higher education institutions

Abstract: Purpose The purpose of this paper is to explore students’ perception and use of English in higher education (HE) institutions in Malaysia. In doing so, it aims to better understand the relationship between students’ perception of English and academic self-efficacy, particularly since English is used as a medium of instruction in HE institutions. Design/methodology/approach Approximately, 980 questionnaires were distributed to four HE institutions to explore relationships and patterns of students perceived En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moreover, in the last item, 12 out of 16 learners also showed their confidence and belief in the term of English mastery. Their agreement to the statement that English mastery was not difficult indicated that they had high self-efficacy to English and thus would bring positive outcome to their learning achievement (Badiozaman, Leong & Jikus (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the last item, 12 out of 16 learners also showed their confidence and belief in the term of English mastery. Their agreement to the statement that English mastery was not difficult indicated that they had high self-efficacy to English and thus would bring positive outcome to their learning achievement (Badiozaman, Leong & Jikus (2019).…”
Section: Discussionmentioning
confidence: 99%
“…These scopes were proven to be contributive to improve the quality and the success of an ELT classroom as shown in some research findings, i.e. perception (Iftanti & Maunah, 2021;Yuntao, 2019;Badiozaman, Leong & Jikus, 2019;Emiliasari & Kosmajadi, 2019;Budianto, 2019), expectation (Loveta, Loeneto, & Vianty, 2020;Eriani, Pratolo, Nailufer & Astuti, 2019;Gadu & Mahsun, 2018), perception and expectation (Halim, et. al, 2021), difficulties (Hajar & Rahman, 2022;Ngoc & Mai, 2020: Patau, 2018.…”
Section: Introductionmentioning
confidence: 93%
“…In the Malaysian context, Badiozaman et al (2019) explained that the 838 undergraduates from four universities generally have a positive perception regarding their academic capabilities in learning ESL although they rated their English language proficiency as low. This study also reported on the strong and positive relationship between students' academic self-efficacy in ESL and their English language competence.…”
Section: Self-efficacymentioning
confidence: 99%
“…This situation has gradually influenced the shift toward English as the medium of instruction in higher education since the passage of the Education Act of 1996, which permitted the use of English as the medium of instruction for technical areas in tertiary education courses (Wan & Sirat, 2018). Consequently, English has emerged as the language of communication and instruction in tertiary education and employment globally (Badiozaman et al, 2019;Chen & Kraklow, 2014;De Costa et al, 2021;Rao, 2019). Since then, English language has been the primary medium of instruction for teaching and learning in most universities in Malaysia, owing to the fact that proficiency in the language is deemed inevitable and fundamental.…”
Section: Introductionmentioning
confidence: 99%